A secure energy trading system for electric vehicles in smart communities using blockchain. (April 2022) - Samuel, Omaji; Javaid, Nadeem; Almogren, Ahmad; Javed, Muhammad Umar; Qasim, Umar; Radwan, Ayman
Highlights: Public and private blockchain is proposed for secure energy trading. Spatial and temporal information-based attacks are avoided using public blockchain. Private blockchain provides efficient energy trading in the smart grids. Differential privacy minimizes the risk of privacy loss. Higher privacy protection of vehicles is attained with a lower information loss. Abstract: In this paper a secure energy system is proposed that consists of private and public blockchains for vehicles in sustainable cities and society. The former protects vehicle owners from spatial and temporal information based attacks while the latter provides efficient energy trading in sustainable cities and society. In the proposed system, the dynamic demand based pricing policy for the vehicle owners is proposed using types of vehicles, time of demand and geographical locations. The vehicles' social welfare and utility are maximized using an optimal scheduling method along with the proposed pricing policy. Also, the vehicle owners' privacy is protected by applying differential privacy in the proposed consensus energy management algorithm. The numerical analyses show that 89.23% reduction in energy price is achieved as compared to 83.46%, 73.86% and 53.07% for multi-parameter pricing scheme (MPPS), fixed pricing scheme and time-of-use pricing scheme (ToU), respectively. Applying the proposed scheme, the owners can achieve about 81.46% reduction in their operating cost as compared to 80.48%, 69.75% and 68.29% for MPPS, fixed pricing scheme and ToU, respectively. Moreover, the proposed system is 60.32% secure as compared to 39.67% for MPPS system. Furthermore, using less information loss against considerable background knowledge of an attacker, higher privacy protection of vehicles is attained.